Teaching Trajectories of Mathematics Teachers: Teachers’ Attitudes Towards Commitment to Students’ Learning - Ghimire, Shree Prasad (Education and Development, 2025)
This research examines the influence of teachers’ years of experience on their attitudes and perceptions towards various aspects of commitment to learners. Using a survey design and a Likert scale as a survey instrument, the data collected from 140 teachers teaching mathematics at Kathmandu-based community and community schools across five experience groups (1-3, 4-6, 7-18, 19-31, and 31+ years), this study analyzes ten dimensions of teacher-student commitment. Results indicate significant variations in attitudes of teachers based on their teaching experience, with mid-career teachers (4-6 and 7-18 years) generally demonstrating the most positive attitudes, while the most experienced teachers (31+ years) often showed the least positive attitudes towards supporting students’ learning. The findings suggest a potential experience-related pattern in teachers’ commitment that may have implications for professional development and educational policy. This study contributes to understanding how teachers’ attitudes change throughout their careers and offers recommendations for sustaining positive engagement with learners across all career stages.